Customer Care Representative Service Strategies for Tourists’ Comfort While Vacationing in Bali: A Case Study at Travel Agent Company X - MAHENDRA, Putu Ferry Krisna; ARTAJAYA, Made; BYOMANTARA, Dewa Gede Ngurah (Journal of Tourism Economics and Policy, 2026)
This study aims to analyze the service strategies implemented by Customer Care Representatives (CCR) to enhance tourists’ comfort while vacationing in Bali. High-quality CCR service is a key determinant of positive travel experiences, particularly amid intensifying competition in the tourism industry. This research employs a descriptive qualitative method, collecting data through interviews, observations, and documentation. Data were analyzed using a SWOT approach and the TOWS strategy matrix to formulate appropriate strategic actions. The findings indicate that service strengths lie in a personalized approach, effective communication, and the use of technologies such as WhatsApp and Google Translate. Identified weaknesses include limited human resources in foreign-language proficiency and the absence of standardized, uniform service procedures. Opportunities arise from strong inbound tourist interest and advances in digital technology, whereas threats stem from competition with online, platform-based services (OTAs). The resulting TOWS strategies include optimizing service digitalization, conducting regular staff training, and strengthening service SOPs. These strategies demonstrably support smooth trip execution and improve tourists’ comfort during their stay in Bali. The study is expected to serve as a reference for tourism industry practitioners—particularly travel agencies—in designing more effective and sustainable service strategies.